The investigation of groove geometry effect on heat transfer for internally grooved tubes - Bilen, Kadir; Cetin, Murat; Gul, Hasan; Balta, Tuba (Pergamon-Elsevier Science Ltd, 2009)
An experimental study of surface heat transfer and friction characteristics of a fully developed turbulent air flow in different grooved tubes is reported. Tests were performed for Reynolds number range 10,000-38,000 and for different geometric groove shapes (circular, trapezoidal and rectangular). The ratio of tube length-to-diameter is 33. Among the grooved tubes, heat transfer enhancement is obtained up to 63% for circular groove, 58% for trapezoidal groove and 47% for rectangular groove, in comparison with the smooth tube at the highest Reynolds number (Re = 38,000). Correlations of heat transfer and friction coefficient were obtained for different grooved tubes. In evaluation of thermal performance, it is seen that the grooved tubes are thermodynamically advantageous (Ns, a < 1) up to Re = 30,000 for circular and trapezoidal grooves and up to Re = 28,000 for rectangular grooves. It is observed that there is an optimum value of the entropy generation number at about Re = 17,000 for all investigated grooves. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Grooves; Ribs; Grooved tube; Heat transfer enhancement/augmentation; Convective heat transfer; Heat exchanger